Gender Bias in Indonesian Endorsed EFL Textbooks: Qualitative Meta-Analysis - Putri Tarisa Ariyani; Nuskhan Abid (IKIP Siliwangi, 2026)
This study examines patterns of gender representation in English as a Foreign Language (EFL) textbooks in the Indonesian context through a qualitative meta-analysis. The study is motivated by the persistence of unequal portrayals in learning materials, despite the national curriculum’s emphasis on equality and inclusivity. Data were collected from scientific articles published between 2015 and 2025 and selected through the PRISMA framework. From this process, three studies that met the inclusion criteria were analyzed through conceptual and thematic synthesis. The findings reveal consistent patterns of imbalance across visual elements, narrative structures, and language use. Male characters are more frequently represented and are commonly associated with active, productive, and prestigious roles in public domains. Female characters tend to appear less frequently and are more often positioned in passive, relational, or domestic roles. In addition, stereotypical patterns are reinforced through the distribution of activities, occupational roles, and linguistic choices. These results suggest that textbooks function not only as instructional materials but also as instruments that reproduce social values aligned with patriarchal ideology. Such representations may influence students’ perceptions of gender roles. Therefore, systematic evaluation and revision of learning materials are necessary to promote more balanced and inclusive representation.